2016
DOI: 10.4103/0366-6999.195473
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Infectious Endophthalmitis

Abstract: Background:Pediatric infectious endophthalmitis is a serious sight-threatening disease for children. The purpose of this study was to investigate the etiology, microbiological spectrum, and visual outcomes of infectious endophthalmitis in children at a single institution in China.Methods:It is a retrospective study of the medical records of all patients under 14 years of age with histories of infectious endophthalmitis, treated at a single institution from January 1, 2009 to January 1, 2015. The clinical chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
3
10
3
Order By: Relevance
“…We observed an increase in the proportion of Gram-positive bacterial infections, while those of Gram-negative bacilli and fungal infections decreased-albeit not significantly-between 2010-2014 and 2015-2018. Most previous studies reported that coagulase-negative staphylococci were the dominant pathogens [14,25,35]. However, we found that Streptococcus was the most prevalent isolate, followed by coagulase-negative staphylococci.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…We observed an increase in the proportion of Gram-positive bacterial infections, while those of Gram-negative bacilli and fungal infections decreased-albeit not significantly-between 2010-2014 and 2015-2018. Most previous studies reported that coagulase-negative staphylococci were the dominant pathogens [14,25,35]. However, we found that Streptococcus was the most prevalent isolate, followed by coagulase-negative staphylococci.…”
Section: Discussioncontrasting
confidence: 45%
“…Most previous studies reported that coagulase-negative staphylococci were the dominant pathogens [ 14 , 25 , 35 ]. However, we found that Streptococcus was the most prevalent isolate, followed by coagulase-negative staphylococci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary age group from 6 to 10 years of age accounts for the highest proportion, similar to the results of some recent studies [13], [14], [12]. Because the percentage of boys with penetrating eye is higher than that of girls, the rate of boys with endophthalmia after penetrating eye also was higher than that of girls [3], [14], [10], [11], [12], [15] . Our report shows that the number of injuries occurring in rural areas was a majority; this result was similar to other reports [3], [13].…”
Section: Discussionsupporting
confidence: 82%
“…1 4 23 24 Higher incidence of endophthalmitis was observed in our study than those of previous adult-dominated studies because children may be less able to recognise or explain their symptoms when injured, and cooperate less well during ocular examination and treatment, leading to increased incidence of endophthalmitis in paediatric patients. 25 Therefore, identification of factors related to endophthalmitis in children with retained IOFB is of great significance for the prevention and timely diagnosis of endophthalmitis following injury.…”
Section: Discussionmentioning
confidence: 99%